2020
DOI: 10.1039/c9ta10405d
|View full text |Cite
|
Sign up to set email alerts
|

Stable artificial solid electrolyte interphase films for lithium metal anode via metal–organic frameworks cemented by polyvinyl alcohol

Abstract: Polyvinyl alcohol (PVA) as a “glue” to cement the metal organic framework (Zn-MOF) sheet as a reasonable artificial SEI film. The artificial SEI film can efficiently adapt to the changes of the volume during the cycle, significantly improve the stability of the Li metal anode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 52 publications
0
51
0
Order By: Relevance
“…To address the fallibilities of lithium metal, numerous strategies have been employed, ranging from designing electrolytes to reduce the number of side reactions between lithium and the electrolyte, [11][12][13][14] engineering hosts that accommodate and control the expansion of lithium, [15][16][17][18][19][20][21] and, in some very recent cases, to incorporating artificial SEIs that passivate the interface between lithium metal and the electrolyte. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Of all the modern strategies employed to passivate lithium metal, artificial SEIs positioned at the Li-electrolyte interface have shown some of the most promising results. Materials such as polymers, [25][26][27] inorganic metal oxides, [27][28][29] inorganic nitrides, [30] fluorides, [31][32][33] nanodiamond, [34] and hybrid structures [35,36] have been applied as interfacial layers, and for the most part, they support uniform plating and stripping of lithium by passivating the reactive Li surface against the electrolyte.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address the fallibilities of lithium metal, numerous strategies have been employed, ranging from designing electrolytes to reduce the number of side reactions between lithium and the electrolyte, [11][12][13][14] engineering hosts that accommodate and control the expansion of lithium, [15][16][17][18][19][20][21] and, in some very recent cases, to incorporating artificial SEIs that passivate the interface between lithium metal and the electrolyte. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Of all the modern strategies employed to passivate lithium metal, artificial SEIs positioned at the Li-electrolyte interface have shown some of the most promising results. Materials such as polymers, [25][26][27] inorganic metal oxides, [27][28][29] inorganic nitrides, [30] fluorides, [31][32][33] nanodiamond, [34] and hybrid structures [35,36] have been applied as interfacial layers, and for the most part, they support uniform plating and stripping of lithium by passivating the reactive Li surface against the electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…To address the fallibilities of lithium metal, numerous strategies have been employed, ranging from designing electrolytes to reduce the number of side reactions between lithium and the electrolyte, [ 11–14 ] engineering hosts that accommodate and control the expansion of lithium, [ 15–21 ] and, in some very recent cases, to incorporating artificial SEIs that passivate the interface between lithium metal and the electrolyte. [ 22–37 ]…”
Section: Introductionmentioning
confidence: 99%
“…ZIF-8 has attracted significant interest for its easy preparation, ordered nanoporous structure, exceptional mechanical stability and ultrahigh chemical stability resulting from the metal-nitrogen bonds [29]. Notably, it was reported that ZIF-8 could withstand metal ion intercalation/deintercalation [30][31][32], preserving its structure/chemical composition intact during cycles. For example, Fan et al introduced a stable artificial solid electrolyte interphase (SEI) film prepared by polyvinyl alcohol (PVA) cementing a metal-organic framework (Zn-MOF), which is beneficial for inhibiting dendrite growth and easing the volume change [30].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, it was reported that ZIF-8 could withstand metal ion intercalation/deintercalation [30][31][32], preserving its structure/chemical composition intact during cycles. For example, Fan et al introduced a stable artificial solid electrolyte interphase (SEI) film prepared by polyvinyl alcohol (PVA) cementing a metal-organic framework (Zn-MOF), which is beneficial for inhibiting dendrite growth and easing the volume change [30]. Li et al reported the commercial LiNi 1/3 Co 1/3 Mn 1/3 O 2 (NCM 333 ) cathode modified by synthesizing ZIF-8 in situ on the surface of NCM 333 , in which ZIF-8 can not only act as a shield against the electrolyte corrosion, but also enable faster lithium-ion transfer at the interfacial regions [31].…”
Section: Introductionmentioning
confidence: 99%
“…But the native SEI layer exhibits low ionic conductivity (4.2 Â 10 À8 S cm À1 ), 10 structural instability and chemical heterogeneity, 11 which induce heterogeneous electrodeposition resulting in dendrite growth. Many studies have disclosed various measures such as use of solid electrolytes or gel electrolytes, 4,8,[12][13][14][15][16] construction of an artificial solid electrolyte interface (SEI) layer, [17][18][19][20][21][22][23]54 design of functionalized separators, [24][25][26][27][28][29][30] and improvement of the structure of current collectors 2,[31][32][33][34][35][36][37] to suppress the formation and growth of lithium dendrites. Construction of an artificial SEI layer is one good solution to solve the challenge of suppressing the formation and growth of lithium dendrites.…”
Section: Introductionmentioning
confidence: 99%